Metacognitive Evaluation Method in Consecutive Interpretation for Novice Learners - Choi, Jung Yoon (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThis research mainly describes the metacognitive evaluation method that can affect both the teaching and learning process of learners, especially novice learners, in consecutive interpretation. The basic idea of this study is to argue that evaluation of novice learners should be based on standards differentiated from those geared towards professional interpreters. The purpose and limitations of evaluation from a pedagogical standpoint are examined, followed by an overview of evaluation in the interpretation classroom. This study is noteworthy in that it attempts to propose a framework for performance assessment and to introduce the learning curve concept as part of assessing the learning process, which are presented as the main elements of the metacognitive evaluation method.